2021
DOI: 10.3758/s13423-021-01966-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictability eliminates neighborhood effects during Chinese sentence reading

Abstract: Previous research has demonstrated effects of both orthographic neighborhood size and neighbor frequency in word recognition in Chinese. A large neighborhood-where neighborhood size is defined by the number of words that differ from a target word by a single character-appears to facilitate word recognition, while the presence of a higher-frequency neighbor has an inhibitory effect. The present study investigated modulation of these effects by a word's predictability in context. In two eye-movement experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The constraint might be particularly useful when the whole compound word is low frequency. Yu et al (2021), however, pointed out that family member sizes are mostly found to be facilitative in alphabetic languages (e.g., Dutch: Kuperman et al, 2009; English: Juhasz & Berkowitz, 2011; Finnish: Kuperman et al, 2008), as well as in Chinese (Yao et al, 2022). Furthermore, when they analyzed only a subset of target words to equate family member size, the inhibitory effect of first character frequency was still present.…”
Section: Discussionmentioning
confidence: 99%
“…The constraint might be particularly useful when the whole compound word is low frequency. Yu et al (2021), however, pointed out that family member sizes are mostly found to be facilitative in alphabetic languages (e.g., Dutch: Kuperman et al, 2009; English: Juhasz & Berkowitz, 2011; Finnish: Kuperman et al, 2008), as well as in Chinese (Yao et al, 2022). Furthermore, when they analyzed only a subset of target words to equate family member size, the inhibitory effect of first character frequency was still present.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al (2023) reported no difference in character-level effects across lexical decision and sentence reading, and on this basis, we predict that facilitatory effects of family metrics may also be observed in sentence reading. However, this may be the case only when target words are unpredictable from the prior context (Yao et al, 2022). If target words are highly predictable, then this may lead to preactivation of the whole word, which may make recognition too rapid for a morpheme-level analysis.…”
Section: Future Directionsmentioning
confidence: 99%